Trechus species from Mt. Choke of northern Ethiopia related to T. niloticus (Quéinnec & Ollivier) with notable male genital morphology (Carabidae: Trechini) - Schmidt, Joachim; Merene, Yeshitla (Zootaxa, 2024)
The Choke Mountain in northern Ethiopia is remarkable due to its highly diverse Trechini fauna. Based on numerous specimens recently collected in the high montane and afroalpine zones along different slopes of Mt. Choke we revise the species related to Trechus niloticus (Quéinnec & Ollivier) and T. reebae (Quéinnec & Ollivier). These species are characterized by probable synapomorphies of the male genitalia and thus may form a natural group. Four species will be newly described which all are endemic to certain parts of the volcano: T. apertus sp. n., T. igori sp. n., T. kniphofia sp. n., and T. yitbareki sp. n. From viewpoint of genital morphology, T. apertus sp. n. is particular remarkable due to the fact that the dorsal ostium of the male genital extends basally across three quarter of the basal bulb. A key to the smaller Trechus species with body size up to 4 mm is presented.